Rezafungin Versus Caspofungin in a Phase 2, Randomized, Double-blind Study for the Treatment of Candidemia and Invasive Candidiasis: The STRIVE Trial. (21st September 2020) - Thompson, George R; Soriano, Alex; Skoutelis, Athanasios; Vazquez, Jose A; Honore, Patrick M; Horcajada, Juan P; Spapen, Herbert; Bassetti, Matteo; Ostrosky-Zeichner, Luis; Das, Anita F; Viani, Rolando M; Sandison, Taylor; et al.
Abstract: Background: Rezafungin (RZF) is a novel echinocandin exhibiting distinctive pharmacokinetics/pharmacodynamics. STRIVE was a phase 2, double-blind, randomized trial designed to compare the safety and efficacy of RZF once weekly (QWk) to caspofungin (CAS) once daily for treatment of candidemia and/or invasive candidiasis (IC). Methods: Adults with systemic signs and mycological confirmation of candidemia and/or IC were randomized to RZF 400 mg QWk (400 mg), RZF 400 mg on week 1 then 200 mg QWk (400/200 mg), or CAS 70 mg as a loading dose followed by 50 mg daily for ≤4 weeks. Efficacy assessments included overall cure (resolution of signs of candidemia/IC + mycological eradication) at day 14 (primary endpoint), investigator-assessed clinical response at day 14, and 30-day all-cause mortality (ACM) (secondary endpoints), and time to negative blood culture. Safety was evaluated by adverse events and ACM through follow-up. Results: Of 207 patients enrolled, 183 were in the microbiological intent-to-treat population ( 21% IC). Overall cure rates were 60.5% (46/76) for RZF 400 mg, 76.1% (35/46) for RZF 400/200 mg, and 67.2% (41/61) for CAS; investigator-assessed clinical cure rates were 69.7% (53/76), 80.4% (37/46), and 70.5% (43/61), respectively. In total, 30-day ACM was 15.8% for RZF 400 mg, 4.4% for RZF 400/200 mg, and 13.1% for CAS. Candidemia was cleared in 19.5 and 22.8 hours in RZF and CAS patients, respectively. No concerning safety trends were observed; ACM through follow-up was 15.2% (21/138) for RZF and 18.8% (13/69) for CAS. Conclusions: RZF was safe and efficacious in the treatment of candidemia and/or IC. Clinical Trials Registration: NCT02734862 Abstract : In a phase 2, randomized, double-blind, multicenter clinical trial conducted to evaluate rezafungin compared with caspofungin followed by fluconazole for primary treatment of patients with proven candidemia or invasive candidiasis, rezafungin demonstrated favorable safety and efficacy.